Vertically Moving Target Localization Based on Interference Feature Matching Using a Single Hydrophone - Chunpeng Zhao; Guolong Liang; Longhao Qiu; Jinjin Wang; Wenfeng Dong (Journal of Marine Science and Engineering)
To address the performance degradation of traditional underwater target localization algorithms in high-speed motion scenarios, this paper proposes a vertically moving localization method based on interference feature matching using a single hydrophone. Due to the overlapping of interference fringes in the time–frequency domain, the method first employs a two-dimensional homomorphic filter to separate different types of interference fringes while removing line-spectrum interference. Then, a theoretical interference period database is constructed, and feature matching is performed on the interference fringes to achieve localization of the vertically moving target. Simulation results show that, under conditions of strong broadband noise and line-spectrum interference, the proposed method effectively separates and restores the interference fringes of high-speed vertically moving targets and successfully locates the moving target under large Doppler conditions. Further validation using field data from Qiandao Lake confirms that the actual measurements align with theoretical analysis, validating the effectiveness of the proposed method.